IMPLEMENTATION OF STRATEGIC POLICY PERFORMANCE FOR TOURISM DEVELOPMENT IN REALIZING COMMUNITY-BASED PUBLIC SERVICES - Eliagus Telaumbanua; Saida Zainurossalamia ZA; Justina Ade Judiarni (Adisam Publisher, 2024)
Tourism development is currently starting to become one of the leading programs in regional development. It is hoped that tourism development will be able to contribute to the receipt of Regional Original Income (PAD) and create jobs in the region. Tourism is a part that plays a role in increasing the income of both countries and regions that have various tourist attractions. Indonesia has abundant natural resources and a wide variety of cultures, so there must be development in the tourism sector. In strategic planning for a tourist destination, environmental analysis and resource analysis are carried out. The purpose of this analysis is none other than to determine the strengths and weaknesses of the organization or institution responsible for tourism development in the tourist destination area. Tourism development can be carried out using a community approach. This approach emphasizes full involvement of the community in the tourism development process. Meanwhile, in providing public services, the community is not only the recipient of public services, but also as an external supervisor. The public has the right to supervise the implementation of service standards provided by each public service provider.